ANALISIS PENGARUH KUALITAS ONLINE WORD-OF-MOUTH DAN KEAMANAN TERHADAP MINAT BELI DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pembelian Produk Fashion di Situs Zalora Indonesia di Semarang) - Adistya, Clara; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2017)
Rapid growth of the internet technology has become one of the aspects that affect people’s lifestyle these days. The increasing usage of internet in Indonesia also gives stimulus toward the entrepreneurs in e-commerce sector to boost online transaction trends. The purpose of this research is to know the impact of WOM online quality, transaction security and online trust toward consumer purchase intention on online shopping transaction. This is done due to a high competition among online shopping sites. This research is also expected to identify what kind of factors that needs to be considered on increasing consumer online purchase intention.The sample used for this research is the visitors of Zalora Indonesia site in Semarang scope who had minimum one-time purchase. The samples are 191 people selected by nonprobability technique with purposive sampling approach. The analysis technique used for this research is structural equation models (SEM).The results of this research indicate that WOM online quality and transaction security have a positive and significant impact toward consumer online purchase intention. Online trust has a positive and significant impact toward consumer online purchase intention. WOM online quality and transaction security have a positive impact but not significant toward consumer online purchase intention.